2010
DOI: 10.1258/ebm.2010.010134
|View full text |Cite
|
Sign up to set email alerts
|

Tracking deposition of a 14C-radiolabeled kudzu hairy root-derived isoflavone-rich fraction into bone

Abstract: Hairy roots were induced in four genotypes from three kudzu species (Pueraria montana var. lobata, P. lobata and P. phaseoloides) in vitro using Agrobacterium rhizogenes to stimulate rapid secondary metabolite synthesis. Hairy roots from P. montana var. lobata (United States Department of Agriculture no. PI 434246) yielded the highest puerarin and total isoflavone content and the greatest new biomass per growth cycle among the genotypes evaluated. Hairy roots from this genotype were selected for radiolabeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Modern pharmacology has demonstrated that puerarin activates blood and eliminates stasis, improves micro-circulation and decreases blood glucose (25,26). Furthermore, it has been shown to have clinical applications in the treatment and management of diabetes, cardiovascular diseases and osteoporosis of post-menopausal women (27)(28)(29). In the present study, STZ-treated rats showed a decrease in femoral BMD compared to normal control rats.…”
Section: Discussionsupporting
confidence: 51%
“…Modern pharmacology has demonstrated that puerarin activates blood and eliminates stasis, improves micro-circulation and decreases blood glucose (25,26). Furthermore, it has been shown to have clinical applications in the treatment and management of diabetes, cardiovascular diseases and osteoporosis of post-menopausal women (27)(28)(29). In the present study, STZ-treated rats showed a decrease in femoral BMD compared to normal control rats.…”
Section: Discussionsupporting
confidence: 51%
“…Some minor malonyl glycosides, such as malonyl daidzin and malonyl genistin, were also reported from Gegen in the past decades [19][20][21]. To our knowledge, there were no C-glycoside malonyl conjugates reported till now.…”
Section: Research Articlementioning
confidence: 75%
“…Furthermore, increasing levels of soy isoflavones had no effect on Ca absorption in postmenopausal women [44,45]. On the other hand, it has been shown that isoflavones reach the bone tissue [46]. Low-dose daidzein induced nucleus ERβ, while 17β-estrogen increased ERα in young piglet bone cells [47].…”
Section: Soy Isoflavones and Bonementioning
confidence: 99%